Increasing seasonality during the early pleistocene in the Mediterranean Sea - G. Crippa; L. Angiolini; F. Felletti; C. Frigerio; M. J. Leng; G. Raineri; M. H. Stephenson (Società geologica italiana, 2014)
The Early Pleistocene is an epoch characterized by several climatic oscillations, with its lower and upper boundaries coinciding respectively with the beginning of the Northern Hemisphere Glaciation and the Middle Pleistocene Transition. During this time interval, the Mediterranean region was strongly affected by rapid climatic changes, the expression of which is clearly recorded by the biotic evolution in fossil archives. One of the most important of these biotic events is the appearance of the boreal guest Arctica islandica at the beginning of the Calabrian Stage, indicating that climatic deterioration had started to affect the Mediterranean Sea. The Arda River marine succession, cropping out in Western Emilia, Northern Italy, continuously covers the Early Pleistocene time interval; it represents an ideal setting to study the climatic oscillations of the Early Pleistocene and, in particular, to understand how seasonality varies during these climate changes. It consists mainly of sandstones intervals, cyclically alternated with siltstones, claystones and very rich fossiliferous beds, deposited in a tectonically active setting during phases of advance of fan deltas affected by high-density flows triggered by river floods. The geochemical signature registered in bivalve shells can be used as an archive of global change in seawater composition and temperature, as these organisms record in their calcium carbonate shells the primary seawater isotope composition, with little or no vital effect. To reach this goal, sclerochemistry has been undertaken on pristine bivalve shells belonging to the species Glycymeris inflata, Glycymeris insubrica and Arctica islandica collected from several stratigraphic horizons throughout the Arda River marine succession. One of the main outcomes of these analyses is the recognition of an increase in the amplitude of the oscillation of the oxygen isotope ratio from the base to the top of the section. This suggests an increase in seasonality in the Early Pleistocene, during the deposition ...